2004
DOI: 10.1017/s1355617704103044
|View full text |Cite
|
Sign up to set email alerts
|

Context-specific memory and apolipoprotein E (ApoE) [varepsilon]4: Cognitive evidence from the NIMH prospective study of risk for Alzheimer's disease

Abstract: The aim of the study was to determine whether the epsilon 4 allele of the apolipoprotein E (ApoE) gene was associated primarily with context-specific memory among individuals at genetic risk for developing Alzheimer's disease. The effect of ApoE status on comprehensive neuropsychological results was examined in 176 healthy adults during baseline cognitive testing in the NIMH Prospective Study of Biomarkers for Older Controls at Risk for Alzheimer's Disease (NIMH Prospective BIOCARD Study). The presence of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
3

Year Published

2004
2004
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 87 publications
2
28
0
3
Order By: Relevance
“…A number of studies have shown that nondemented older adults with a positive family history for AD perform significantly worse than those with a negative family history on tests of episodic memory (Bondi et al 1994;Caselli et al 2004;La Rue et al 1992;Levy et al 2004). …”
Section: Neuropsychological Studies Of the Prodromal Period Of Alzheimentioning
confidence: 99%
“…A number of studies have shown that nondemented older adults with a positive family history for AD perform significantly worse than those with a negative family history on tests of episodic memory (Bondi et al 1994;Caselli et al 2004;La Rue et al 1992;Levy et al 2004). …”
Section: Neuropsychological Studies Of the Prodromal Period Of Alzheimentioning
confidence: 99%
“…For instance, ε3/3 homozygotes with a +FH have a 30% chance of developing AD, whereas ε3/4 heterozygotes with a +FH have a 46% lifetime risk and ε4/4 homozygotes with +FH have a 61% likelihood of developing AD . Cognitively, several studies have shown that nondemented older adults with a positive family history for AD perform significantly worse than those with a negative family history on tests of episodic memory (Bondi et al, 1994;Caselli et al, 2004;La Rue et al, 1992;Levy et al, 2004).…”
Section: Functional Mri Patterns Of Activity Associated With Risk Of mentioning
confidence: 99%
“…Cross-sectional studies provide evidence for lower cognitive test scores among ApoE -4 carriers vs. non-carriers. For example, cross-sectional studies of cognitively normal middle-aged and older adults have reported lower performance among ApoE -4 carriers compared to non-carriers on tests of episodic memory [17], verbal fluency [18], and attention [19]. However, cross-sectional cognitive differences as a function of ApoE genotype are not always evident, particularly in studies that largely focus on middle-aged (45 - 65 years) individuals [20-23].…”
Section: Introductionmentioning
confidence: 99%